PENGARUH CUSTOMER RELATIONSHIP MARKETING DAN BRAND TRUST TERHADAP CUSTOMER LOYALTY PADA PT. ASURANSI JIWASRAYA (PERSERO) CABANG PEKANBARU - Verawati Pasaribu; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The development of business nowadays claim theirself to give the best and to do the improvement not only for the service but also their product. The dinamyc competition enable the business not to find the new customer, but to defend them for a loyal so that they don’t interest to the other business. One of the customer loyalty strategy is Customer Relationship Marketing and Brand Trust. This reserach analyzes the influence of Customer Relationship Marketing and Brand Trust to Customer Loyalty on PT. Asuransi Jiwasraya (Persero) branch Pekanbaru.This research use the questioner with Likert scale analized by validity, reliability,doubled linear regressionanalysis, determination coefficient, individual signification (t experiment),simultaneous (F experiment) with SPSS 20 application. There are 96 sample on this research where the calculation using Slovin formula.The trial show that customer relationship marketing and brand trust make the positive and significant influence to customer loyalty. Determination coefficient (R2) show that customer relationship marketing and brand trust variable influence 83% tocustomer loyalty variable, while the 17% influenced by the other variable that not include on this reserach.Keywords: Customer Relationship Marketing, Brand Trust, Customer Loyalty